CANDIDA INTERTRIGO IN A PATIENT ON ICU POSITIVE TO COVID19 - Trajkova Vesna; Dimitrovska I; Hristina Breshkovska; Tusheva Ivana; Rexhepi Ruzhdi (Association of the Albanian Doctors from Macedonia, 2021)
Intretigo is a common dermatological manifestation caused by occlusive conditions in skin folds increasing local heat and moisture and skin-on-skin friction. We present a 58-year-old woman with intertrigo hospitalized in Intensive Care Unit (ICU) due to severe COVID-19 infection. Intertrigo was localized on large areas on the body, mostly genitocrural area, axillary area and sub-mammary folds, but also on the trunk, arms and legs. During COVID-19 treatment mechanical ventilation was applied; nasogastric tube was placed and the patient was treated with intensive COVID-19 therapy. Intravenous Fluconasole 200 mg helped improving the skin condition. While most of intertigo is benign disease and it is not difficult to treat it is important to be aware of the dermatologic manifestations and complications during COVID- 19 patients and properly treat complications.
Keywords: COVID-19; Intertrigo; Pneumonia; SARS-CoV-2; Skin